A modeling study of Patos lagoon (Brazil) flow response to idealized wind and river discharge: dynamical analysis (Brazilian Journal of Oceanography, 2006)
A three-dimensional numerical model is used to investigate the Patos Lagoon flow response to idealized northeasterly winds and river inflow. North of Ponta da Feitoria, in the central lagoon, the main balance in the alongshore direction at steady state is between the surface stress and the pressure gradient, with a small contribution from the bottom stress. The alongshore variability in the pressure gradient is balanced by the Coriolis acceleration. In the cross-shore direction, the balance is nearly geostrophic, with deviations from that balance in the shallow regions, where the bottom stress term makes a significant contribution. Close to headlands, nonlinear terms are also important, leading to an additional increase in the cross-shore pressure gradient. Relaxation events were found to be important for seiche generation in the central lagoon. Close to the lagoon's mouth, nonlinear terms were found to be the major terms balancing the pressure gradient generated in response to the wind forcing. After the wind relaxation, the pressure gradient in the estuarine region is reversed, driving a landward flow. River inflow acts to dampen out the generation of seiches following wind relaxations. A river inflow Q = 2000 m³ s-1 was found to be sufficient to shut down the landward flow generated following relaxation events.